The Cultural Conditioning of the Polish Reception of the Czech Cimrman Hoax - Németh Vítová, Lenka (Bohemistyka, 2025)
The Polish audiences have first encountered the Czech Cimrman hoax in the 1970s, and after an almost twenty-year break, Cimrman returned to them after the turn of the millennium. Despite the admirably rich encounter with Czech culture (and especially its satire) among Polish audiences after 1989, the plays of the Jára Cimrman Theatre (Divadlo Járy Cimrmana) and the history of this hoax are known only to a small group of enthusiasts. The diverse standpoints of Polish literary reflection characterize Cimrman’s hoax as rooted in the Czech cultural tradition following its ambitions. Cimrman started as a specific game of hoax played out between the authors and their audience, but otherwise also as a therapeutic folksiness leading to spiritual emptiness and a contradictory questioning, which modernised national revivalist ideals. The lack of understanding of the Cimrman hoax among Polish audiences could be explained by the focus on different aspects of the phenomenon. However, in my opinion, there are other important reasons for the difficulties in transporting this Czech phenomenon into the Polish cultural context. I have encountered the following three issues: the different role played by hoax in both cultures, the discrepancy in the assessment of the Austro-Hungarian period, and the different understanding of the ideals and aesthetics of the Sokol movement. I interpret this according to Hayden White’s approach – viewing cultural differences as beneficial, as an opportunity to learn something new from these differences.